Advanced Public Speaking - Meade, Lynn (Open textbook library., 2021)
This advanced public speaking textbook is designed to encourage you as a speaker and to help you sharpen your skills. It is written to feel like you are sitting with a trusted mentor over coffee as you receive practical advice on speaking. Grow in confidence, unleash your personal power and find your unique style as you learn to take your speaking to the next level--polished and professional.